Marginalizing the Law. Corporate Social Responsibility, Worker Hotlines and the Shifting Grounds of Rights Consciouness in Contemporary China - Hertz, Ellen (My University, 2016)
Based on two years of research in Taiwan and mainland China, this paper argues that the introduction of corporate social responsibility capacity building programs into Chinese civil society has significantly altered NGOs’ relation to legal notions of social and human rights. While increased reference to law and legal instruments is common in popular struggles for social justice, the CSR paradigm can lead to very different forms of rhetoric and practice, shifting responsibility for avoiding violations of the law in transnational supply chains to supplier factories and indeed to workers themselves. Furthermore, the urban-based “civilizational project” aimed at teaching new norms of behavior and attitude to the largely rural working class population in contemporary China intersects with Western-sponsored capacity building programs to promote labor-rights consciousness in particular ways, producing loci for the spread of notions such as personal development and family counseling in lieu of rights advocacy.
Keywords: Corporate social responsibility P.R.C.; Legal innovation; Human rights; Personal development